Neoadjuvant chemoimmunotherapy in patients with locally advanced squamous head and neck cancer: A retrospective study - Huang, Qiu-Yi; Xu, Ling-Feng; Wu, Yuan; Chen, Jian (Frontiers in Oncology, 2025)
BackgroundThe conventional approach for the treatment of locally advanced head and neck squamous cell carcinoma (HNSCC) entails the combination of surgery with radiotherapy or chemoradiotherapy. However, the survival rate of patients has not improved. This is frequently attributed to the strong invasive and metastatic capabilities of the tumor, which makes it prone to recurrence. In recent years, neoadjuvant chemoimmunotherapy has emerged as a focal point of research. This is primarily due to its remarkable enhancement of the pathological response rate and patient survival. The objective of this study was to conduct a retrospective analysis to evaluate the safety and efficacy of neoadjuvant chemoimmunotherapy in locally advanced HNSCC.MethodsThe clinical data of 82 patients with HNSCC, who underwent surgery subsequent to neoadjuvant chemoimmunotherapy during the period from January 1, 2019, to May 31, 2024, were retrospectively incorporated in this study. Analyses were conducted on the pathological response rate, survival data, and adverse events associated with the treatment.ResultsThis study enrolled 82 patients in total. The oral cavity was the site of malignancies in 41, 50.0% of the cases. Nearly half of the patients (32, 39.0%) were treated with two cycles of neoadjuvant chemoimmunotherapy, while the remaining patients received three or more cycles. 78 patients (95.1%) achieved R0 resection and 65 patients (79.3%) achieved objective response rate (ORR). The pathological complete response (pCR) rate was 25.6% [95% confidence interval (CI), 15.3%–35.1%], and the major pathological response (MPR) rate was 41.5% (95% CI, 30.4%-52.0%). All patients demonstrated good tolerance of neoadjuvant therapy, with a grade 3/4 treatment-related adverse event rate of 14.6%. After a median follow-up of 16 (3–48) months, the 1-year disease-free survival rate was 80.5% (95%CI: 72.4%- 88.6%) and the 1-year overall survival rate was 93.7% (95%CI: 88.7%-99.14%).ConclusionsNeoadjuvant chemoimmunotherapy significantly improves the pathological response rate and R0 resection rate in patients with locally advanced HNSCC with a low incidence of treatment-related adverse events, and our findings suggest its potential as a treatment strategy for locally advanced HNSCC.